2012
DOI: 10.1007/s00401-012-1042-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical mapping of the human hippocampus reveals perisynaptic matrix around functional synapses in Alzheimer’s disease

Abstract: Perineuronal matrix is an extracellular protein scaffold to shape neuronal responsiveness and survival. Whilst perineuronal nets engulf the somatodendritic axis of neurons, axonal coats are focal extracellular protein aggregates surrounding individual synapses. Here, we addressed the chemical identity and subcellular localization of both perineuronal and perisynaptic matrices in the human hippocampus, whose neuronal circuitry is progressively compromised in Alzheimer's disease. We hypothesized that (1) the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 73 publications
(130 reference statements)
7
69
1
Order By: Relevance
“…Animals were routinely perfusion‐fixed with 4% PFA in 0.1M PB (pH 7.4) under deep anesthesia as described (Alpár et al , 2014; Lendvai et al , 2013; Mulder et al , 2009; Romanov et al , 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Animals were routinely perfusion‐fixed with 4% PFA in 0.1M PB (pH 7.4) under deep anesthesia as described (Alpár et al , 2014; Lendvai et al , 2013; Mulder et al , 2009; Romanov et al , 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Aggrecan, cartilage link protein Crtl1 and tenascin-R have been identified as the main protective components of PNNs against iron-induced oxidative stress or Alzheimer's disease (AD) pathology [14,65]. The recent study of Lendvai et al [15] showed preserved ACs and increased brevican and Crtl1 expression in AD patients and transgenic APdE9 mice; this suggests an increased turnover of ECM molecules to maintain synaptic integrity.…”
Section: Role Of the Extracellular Matrixmentioning
confidence: 99%
“…The finding that ECM digestion increases performance in reversal learning without affecting already learned capacities brings forth the interesting challenge of guiding plastic changes using controlled ECM modulation [63]. On the other hand, mature PNNs and perisynaptic ACs create a protective shield attenuating the neurodegeneration evoked by neurotoxicity, oxidative stress or Ab deposits [14,15,65]. Aggrecan, cartilage link protein Crtl1 and tenascin-R have been identified as the main protective components of PNNs against iron-induced oxidative stress or Alzheimer's disease (AD) pathology [14,65].…”
Section: Role Of the Extracellular Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromogenic or multiple immunofluorescence histochemistry with select combinations of primary antibodies (Table S4) (1,34,35,49,51,(66)(67)(68)(69)(70)(71)(72)(73)(74) was performed according to published protocols (67). Results of chromogenic histochemistry were captured on an Olympus BX-51 microscope.…”
Section: Methodsmentioning
confidence: 99%